2022
DOI: 10.3389/fphar.2022.1040154
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics profiles, pharmacological properties, and toxicological risks of dehydroevodiamine: A review

Abstract: Dehydroevodiamine (DHE) is a quinazoline alkaloid isolated from Evodiae Fructus (EF, Wuzhuyu in Chinese, Rutaceae family), a well-known traditional Chinese medicine (TCM) which is clinically applied to treat headache, abdominal pain, menstrual pain, abdominal distension, vomiting, acid regurgitation, etc. Modern research demonstrates that DHE is one of the main components of EF. In recent years, DHE has received extensive attention due to its various pharmacological activities. This review is the first to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Numerous studies have reported the significant cognitive‐enhancing effects of dehydroevodiamine in various cognitive impairment models. It has also demonstrated good blood–brain barrier permeability 52 . In 2000, Park et al .…”
Section: Current Status Of the Main Alkaloid Components Of Evodia In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported the significant cognitive‐enhancing effects of dehydroevodiamine in various cognitive impairment models. It has also demonstrated good blood–brain barrier permeability 52 . In 2000, Park et al .…”
Section: Current Status Of the Main Alkaloid Components Of Evodia In ...mentioning
confidence: 99%
“…It has also demonstrated good blood-brain barrier permeability. 52 In 2000, Park et al conducted the initial study on the therapeutic effects of orally administered dehydroevodiamine in various rat models of cognitive impairment. The results showed that oral administration of dehydroevodiamine significantly improved cognitive impairments induced by scopolamine in an AD rat model.…”
Section: Dehydroevodiaminementioning
confidence: 99%
“…In toxicity studies, it was found that it can promote arrhythmia and impair bile acid homeostasis without hepatotoxicity. Studies of long‐term and high‐dose toxicity in animal models, however, remain blank and need further research (Fu et al, 2023). Nie et al analyzed Dendrobium nobile Lindl alkaloid (DNLA) ( 78 ) extracted from Dendrobium nobile by LC–MS/MS and determined that alkaloids accounted for 79.8% of DNLA and identified the structure and proportion of various alkaloids (Nie et al, 2016).…”
Section: Natural Alkaloids With the Activity Of Treating Cns Diseasesmentioning
confidence: 99%
“…In toxicity studies, it was found that it can promote arrhythmia and impair bile acid homeostasis without hepatotoxicity. Studies of long-term and high-dose toxicity in animal models, however, remain blank and need further research(Fu et al, 2023).Nie et al analyzed Dendrobium nobile Lindl alkaloid (DNLA) (78) extracted from Dendrobium nobile by LC-MS/MS and determined that alkaloids accounted for 79.8% of DNLA and identified the structure and proportion of various alkaloids(Nie et al, 2016). In later studies, the team found that DNLA improved cognitive deficits in aged SAMP8 mice by downregulating the stress-related PERK signaling pathway by inhibiting cal-pain1, GSK-3β, and CDK5 activities and ultimately reducing tau hyperphosphorylation(Liu et al, 2020).…”
mentioning
confidence: 99%
“…20 Recent studies have shown that DHE has good pharmacological activity and it is expected to become a potential therapeutic drug for the treatment of Alzheimer's disease, chronic stress, amnesia, chronic atrophic gastritis, gastric ulcers, and rheumatoid arthritis. 21 Moreover, DHE has demonstrated significant antitumor activity in various cancers, including colorectal cancer (CRC) and gastric cancer. 22 However, the therapeutic effect of DHE on liver cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%